O-205 Night shift work and sleep deprivation in relation to vaccine induced SARS-CoV-2 antibody responses in a general population cohort (COVICAT study). (14th March 2023) - Papantoniou, Kyriaki; Espinosa, Ana; Karachaliou, Marianna; Aguilar, Ruth; Harding, Barbara; Palomar-Cros, Anna; Castaño-Vinyals, Gemma; Straif, Kurt; Moncunill, Gemma; Cid, Rafael de; Dobaño, Carlota; Garcia-Aymerich, Judith; et al.
Abstract : Introduction: Night shift work and sleep deprivation have been associated with lower antibody responses induced by vaccination against seasonal influenza, meningitis-C and hepatitis A. We examined the association of exposure to night shift work and sleep deprivation with antibody levels induced by COVID-19 vaccines. Materials and Methods: This study was nested in an ongoing population-based cohort in Catalonia, Spain. Blood samples were collected in 2021 from a random subsample of 1, 090 participants. We measured 3 immunoglobulins (Ig)M, IgG, and IgA antibodies against 5 SARS-CoV-2 antigens, including RBD (receptor-binding domain), S (spike-protein), and S2 (subunit 2 from spike-protein). We collected data on night shift work (current night work, frequency, duration) and sleep metrics (sleep duration, sleep problems, changes in sleep duration since the beginning of the pandemic). We adjusted linear regression estimates (% change) for individual- and area-level covariates, time since vaccination, vaccine doses and type. Analyses were restricted to participants without previous COVID-19 infection (N=639). Infection status was defined using questionnaires, SARS-CoV-2 test registry and serology information (seropositivity to N-antigen). Results: Participants' mean age was 57.6 years, 57% were female, 73% received 2 vaccine doses (42% Pfizer, 44% AstraZeneca), 5.8% were current night workers and 36.5% of the sample reported sleep problems. No overall association pattern was observed between current? night work and vaccine-induced antibody responses. IgG levels tended to be lower (differences in the range of 3.6–53.7%) among night workers, compared to day workers but differences were not statistically significant. Participants with short sleep (<=6 hours) had significantly lower IgM antibody levels compared to those that reported 7 hours of sleep. No clear pattern was observed with sleep quality. Conclusions: Further research in larger studies is needed to evaluate the influence of night shift work and impaired sleep on vaccine induced immune responses and risk of breakthrough infections.